INTEGRATING CLINICAL REASONING INTO INTENTIONAL ROUNDING: A SYSTEMATIC REVIEW OF NURSING INTERVENTIONS AND OUTCOMES - Nur Aslinda; Dyah Wiji Puspita Sari; Muh Abdurrouf; Nopi Nur Khasanah (Jurnal Ilmu Kesehatan & Kebidanan Nusantara, 2026)
Intentional rounding (IR) is a structured nursing intervention designed to enhance patient monitoring and safety through periodic bedside visits. However, its effectiveness remains a subject of debate, particularly regarding the application of clinical reasoning during implementation. This systematic review aims to synthesize evidence concerning IR interventions and outcomes, emphasizing the integration of clinical reasoning into nursing practice. The review was conducted in accordance with PRISMA 2020 guidelines. Searches were performed across MEDLINE/PubMed, CINAHL, EMBASE, and Scopus for the period of January 2016 to July 2026. Of 175 records identified, 32 duplicates were removed, 143 studies were screened, and five studies met the inclusion criteria. Due to methodological heterogeneity, a narrative synthesis was conducted. IR demonstrated benefits for patient safety, notably a reduction in fall incidents; however, its impact on pressure ulcers and call bell usage was not significant. A gap was identified between documentation compliance and clinical fidelity, highlighting a risk of "tick-box" practice driven by workload and documentation demands. The quality of communication and nurses' cognitive engagement emerged as critical factors in IR effectiveness. While IR has the potential to improve patient safety, its effectiveness relies on the integration of clinical reasoning, high-quality communication, organizational support, and a reduction in documentation burden.